The Effect of Acupressure Therapy on Menstrual Pain Intensity - Siti Nabilah; Resi Galaupa (East Asian Journal of Multidisciplinary Research, 2022)
Reproductive health of young women is not only a sexual problem but also involves all aspects of reproduction, including secondary sex development, which includes soft voice, enlarged breasts, enlargement of the hip area, and menarche. Therefore, this research aims to know the effect of acupressure therapy on the intensity of menstrual pain in female students at STIKes Yatsi Tangerang. This  type  of  research  is  a  quasi-experimental  research that design  isuses  basedion  igroup  ipre-test  iand  ipost-test.  iThe  ipopulation  iin  ithis  istudy  iwas  ia  iLevel  iII  iMidwifery  istudent  iat  iSTIKes  iYatsi.  Besides, the research was carried out in March 2022. Eventually, there is a change in menstrual pain in second-level female students at STIKes Yatsi before and after acupressure therapy.